Out of sight: volunteering in remote locations in Western Australia in the shadow of managerialism - Holmes, Kirsten; Brueckner, M.; Pick, David (Australian and New Zealand Third Sector Research Inc., 2017)
Recent years have seen a trend towards ‘professionalising’ volunteering in Australia to enhance the effectiveness and accountability of volunteer organisations. These changes are part of the emergence of neoliberal-inspired managerialist logics that support the introduction of businesslike practices that emphasise efficiency, strategy and competitiveness and a strong focus on volunteer management. This paper examines experiences of volunteers operating in remote regions of Western Australia and problematises the seeming disconnect between their needs and aspirations and what can be seen as the managerialisation of volunteering. The intention is to stimulate discussion about the future direction of volunteering in Australia and the unintended consequences of the managerialist agenda.